2012
DOI: 10.5846/stxb201012211822
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of rainfall interception for four typical shrubs in Qilian Mountain

Abstract: Rainfall intercepting by vegetation plays an important role affecting the water balance at local and catchment scale due to the control that vegetation canopy exert by modifying both evaporation and the redistribution of incident rainfall. Qilian Mountain is source regions of Heihe River, Shiyang River and Shule River inland river basin. In consideration of widespread shrubs which account for 68% of the whole forest area of Qilian Mountain, the research on rainfall interception process of shrubs for understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The throughfall percentage of A. splendens is 70.58% (Jiang, 2016), which is greater than that of four typical shrubs in the Qilian Mountains (52.3% to 63.5%) (Liu et al, 2012) and shrubs in global drylands (63%) (Magliano et al, 2018). The canopy architecture of semiarid shrubs serves as an effective funnel to channel stemflow to the root zone and promotes rainfall infiltration (Peng et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…The throughfall percentage of A. splendens is 70.58% (Jiang, 2016), which is greater than that of four typical shrubs in the Qilian Mountains (52.3% to 63.5%) (Liu et al, 2012) and shrubs in global drylands (63%) (Magliano et al, 2018). The canopy architecture of semiarid shrubs serves as an effective funnel to channel stemflow to the root zone and promotes rainfall infiltration (Peng et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…The observations of T f and S f did not apply in SH. However, other studies have found that IL accounted for approximately 35% of ET in shrublands (Liu et al, 2012;Ma et al, 2017). Therefore, combined with the observed ET and P values in SH, a b value of 0.142 was obtained in SH in this study.…”
Section: Canopy Interception (Il)mentioning
confidence: 94%
“…Vegetation is rare in this region, and the vegetation coverage is extremely low (Liu et al, 2012(Liu et al, , 2014.…”
Section: Study Areamentioning
confidence: 99%
“…This aquifer groundwater is typically discharged to various tributaries in the form of springs near the rivers at the foot of the slope. In this region, alpine meadows are the main vegetation type (Liu et al, 2012;Chen et al, 2014a;Liu et al, 2014).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation